E‐Skin Piezoresistive Pressure Sensor Combining Laser Engraving and Shrinking Polymeric Films for Health Monitoring Applications. Issue 21 (11th October 2021) - dos Santos, Andreia; Fortunato, Elvira; Martins, Rodrigo; Águas, Hugo; Igreja, Rui
Abstract: Electronic‐skin (e‐skin) is pursued, as of the 21st century, to mimic the sensory capabilities of human skin for several applications. Pressure is one of the key stimuli in e‐skin technology, frequently detected using piezoresistive sensors, which consist of film layers commonly micro‐structured to improve their performance, either through expensive photolithography techniques or other poorly customizable approaches. The authors' group recently introduced laser engraving as a low‐cost yet highly customizable micro‐structuring technique to produce molds, despite the limited resolution. Combining laser engraving with shrinking polymeric films (SPFs) to fabricate molds is an innovative strategy to greatly improve the performance of the sensors, allowing for thinner and highly conformal sensor layers while minimizing costs. Shrinking these SPFs after their engraving yields smaller yet high aspect ratio cavities. Herein, all the laser engraving parameters are thoroughly investigated to optimize SPF molds (arrays of 10 µm vertical lines spaced by 200 µm, engraved with 3% laser power, 25% speed, and 0.04'' between laser and substrate) to produce e‐skin piezoresistive sensors with a sensitivity of −1.4 kPa −1 below 10 kPa, a 1.4 ms recovery time, and a capability to detect distinct body movements, illustrating the great potential for health monitoring applications. Abstract : This work explores the innovative combination of laser engraving with shrinking polymeric films (SPFs, as molds) to micro‐structure polymeric films that integrate electronic‐skin pressure sensors. After shrinking the engraved SPFs molds, it is possible to obtain small structures with a high aspect ratio, allowing the sensors to be thin and conformal, and thus be suitable for health monitoring applications.